Religion and the global city - Garbin, David; Strhan, Anna (New York Bloomsbury Academic, 2017)
Introduction, David Garbin (Senior Lecturer in Sociology, University of Kent, UK) and Anna Strhan (Lecturer in Religious Studies, University of Kent, UK) -- Part One: Power, visibility and the politics of space -- 1. On the Road: Pentecostal Pathways through the Mega-City, Simon Coleman (Chancellor Jackman Professor, University of Toronto, Canada) and Manuel A. Vásquez (Professor of Religion, University of Florida, USA) -- 2. Urban Planning and Secular Atheism in Shanghai, Beijing, and Singapore, Peter van der Veer (Director of the Max Planck Institute for the Study of Religious and Ethnic Diversity, Göttingen, and University Professor at Large, Utrecht University, Netherlands) -- 3. Occupying the Global City: spatial politics and spiritual warfare among African Pentecostals in Hong Kong, Benjamin Kirby (University of Leeds, UK) -- 4. Pentecostal Productions of Locality: Urban Risks and Spiritual Protection in Cape Town, Marian Burchardt (Post-doctoral Researcher, Max Planck Institute for the Study of Religious and Ethnic Diversity, Germany) -- Part Two: Religious media, publics, and global cultural flows -- 5. 'The Future as news': Astrology and mediated religion in Global Bangalore, Sahana Udupa (Associate Professor, Central European University, Hungary, and Senior Research Partner, Max Planck Institute for the Study of Religious and Ethnic Diversity, Germany) -- 6. Theorizing Mediatization and Religious Agency in European Global Cities, David Herbert (Professor of Sociology, Kingston University, UK and Professor of Religion and Society, University of Agder, Norway) -- 7. Godlessness in the Global City, Lois Lee (Lecturer in Secular Studies, University of Kent, UK) -- Part Three: Centralities, peripheries, and religious reterritorialization -- 8. Marching for Jesus in Paris: Religious territorialization, public space, and the appropriation of centrality in a fragmented city, Yannick Fer (CNRS Researcher, GSRL, France) and Gwendoline Malogne-Fer (post-doctoral research student, GSRL, CNRS-EPHE, France) -- 9. Transnational religion, multiculturalism, and global suburbs: a case study from Vancouver, Claire Dwyer (Reader in Geography and Co-Director of the Migration Research Unit, University College London, UK) -- 10. Place And The (Un-)Making Of Religious Peripheries: Weddings Among Kenyan Pentecostals In London,Leslie Fesenmyer (ESRC Future Research Leaders Fellow at COMPAS, University of Oxford, UK) Part Four: Global migration, everyday multiculturalism, and religious place-making -- 11. At Home in The Multicultural City: Islam and Religious Place-Making in Stuttgart, Germany, Petra Kuppinger (Professor of Anthropology, Monmouth College, USA) -- 12. Religion as 'urban white noise' - material practices of everyday religion at the 'unquiet frontiers' of the hyper-diverse city, Chris Baker (William Temple Professor of Religion and Public Life, University of Chester, UK and Director of Research for the William Temple Foundation) -- 13. Between wandering and staying put: Piety and urban mobility among young Somali women in multicultural London, Giulia Liberatore (Leverhulme Early Career Fellow at COMPAS and Junior Research Fellow at Linacre College, University of Oxford, UK) -- 14. Religion, Migration, and the 'Worlding' of Urban Daily Life: Local and Transnational Pentecostalism in Rio De Janeiro, Gerda Heck (Assistant Professor of Sociology and Migration and Refugee Studies, American University in Cairo, Egypt) and Stephan Lanz (Senior Lecturer, Europa-Universität Viadrina, Germany) -- Bibliography -- Index.
"This is the first book to explore how religious movements and actors shape and are shaped by aspects of global city dynamics. Theoretically grounded and empirically informed, Religion and the Global City advances discussions in the field of urban religion, and establishes future research directions. David Garbin and Anna Strhan bring together a wealth of ethnographically rich and vivid case studies in a diversity of urban settings, in both Global North and Global South contexts. These case studies are drawn from both 'classical' global cities such as London and Paris, and also from large cosmopolitan metropolises - such as Bangalore, Rio de Janeiro, Lagos, Singapore and Hong Kong which all constitute, in their own terms, powerful sites within the informational, cultural and moral networked economies of contemporary globalization. The chapters explore some of the most pressing issues of our times: globalization and the role of global neo-liberal regimes; urban change and in particular the dramatic urbanization of Global South countries; and religious politics and religious revivalism associated, for instance, with transnational Islam or global Pentecostal/Charismatic Christianity."--Bloomsbury Publishing
Includes bibliographical references and index
Reproduktion
Barrierefreier Inhalt: Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Keywords: Globalization -- Religious aspects; Cities and towns -- Religious aspects; Electronic books; Aufsatzsammlung; Konferenzschrift -- 2014 -- Brighton